Detention as a violation of the fundamental right to protection - Lototskyi M.; Dzundza L. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of the work is to study the current legislation that violates a person’s fundamental right to protection when the preventive measure of detention is chosen for him. Method. The methodology includes a comprehensive analysis and generalization of the available scientific and theoretical material and the formulation of relevant conclusions. During the research, the following methods of scientific knowledge were used: comparative-legal, logical-grammatical, systemic-structural, modeling. The results. In the course of the research, it was recognized that in the criminal procedural legislation of Ukraine, the application of a preventive measure, both at the stage of pre-trial investigation and during the consideration of a criminal case in court, detention in custody violates the fundamental right of a person to protection, in particular the right to collect evidence, the equality of parties in criminal proceedings proceedings, which in turn violates the right to a fair trial. Scientific novelty. In the process of research, it is scientifically substantiated that the criminal procedural legislation of Ukraine as a whole corresponds to the Basic Law of Ukraine and the practice of the European Court of Human Rights when bringing a person to criminal responsibility, however, the application of one of the most severe preventive measures of detention to a person/persons violates it the right to protection, resulting in the violation of other rights of the person. Practical significance. The results of the research can be used in law-making activities for the further improvement of the national criminal procedural legislation regarding the improvement of the institution of the application of preventive measures, as well as in the educational process during the teaching and learning of the academic disciplines “Criminal Procedural Law of Ukraine”, “Criminal Law”, “Law Enforcement Activities” , “Advocacy”, others.